A microstructural investigation on deformation mechanisms of Fe–18Cr–12Mn–0.05C metastable austenitic steels containing different amounts of nitrogen. (5th October 2015) - Kermanpur, A.; Behjati, P.; Han, J.; Najafizadeh, A.; Lee, Y.-K.
Graphical abstract: Highlights: Deformation mechanism of Ni-free austenitic steels includes γ → ε-martensite → α′-martensite. Formation of the ε-martensite is significantly enhanced by the N content. Increased deformation temperature reduces the formation of ε-martensite. Abstract: Deformation mechanisms of the Ni-free Fe–18Cr–12Mn–0.05C (wt%) austenitic steels containing 0, 0.25 and 0.44 N were investigated. Effects of N addition, strain and temperature on the formation of deformation-induced ε- and α′-martensite phases were determined using transmission electron microscopy and electron back-scattered diffraction techniques. Based on the microstructural evolutions, it is proposed that deformation mechanism of these steels includes the sequence of γ → ε-martensite → α′-martensite, in which the formation and stability of the ε-martensite is significantly enhanced by the N content. Increased deformation temperature from 298 to 373 K reduces the formation of ε-martensite (more than 80%).